Studi Evaluatif Terhadap Pelatihan Manajerial Bagi Penyuluh Keluarga Berencana Di Perwakilan BKKBN DIY Tahun 2019 - Anggraeni Wulandari; Aloysius Utomo Budi Santoso (Pancanaka, 2020)
Evaluative studies important in assessing training implementation. This research using Kirkpatrick's Evaluation Model, focuses on evaluation level 3 (behavior) and 4 (results) after Managerial Training for Field Workers at BKKBN DIY 2019. The analysis uses cross tabulation and field observations. The sample was 82 field workers participants for Managerial Training at the BKKBN DIY in 2018 who took part in remedial certification in 2018 also filled out online evaluation form. The evaluation of level 3, 42.7% of participants in the DS category, stated that the material received by the class during the training was "easy to apply". Then 45.1% of participants in the DS category stated that they "turned out well" in experiencing changes in behavior after the training and 46.3% of participants in the DS category stated that they were "motivated" to apply the material in field. Evaluation level 4 show there is no correlation: "remedial score" with "ease of material application in the field"-"changes in behavior after training"-"motivation to apply material in the field". Self-efficacy affects field workers graduation in remedial certification. Managerial training and certification need to be better designed especially the material and certification questions, so it is suitable with daily field work of field workers.